Erlang for Concurrent Programming. - LARSON, JIM (Communications of the ACM, 2009)
The article discusses the use of the Erlang computer programming language. Erlang, a general-purpose concurrent programming language and runtime system, can be a valuable tool in solving concurrent problems, the article states. It was developed in the 1980s by the Swedish telecommunications company Ericsson for managing phone switches. Other topics include Erlang's minimal set of concurrency primitives, its natural fit in distributed Internet server applications, and its use in graphical user interfaces and ordinary batch applications.